Polymorphisms in the SNRPN gene are associated with obesity susceptibility in a Spanish population. (May 2017) - Albuquerque, David; Manco, Licínio; González, Luz M.; Gervasini, Guillermo; Benito, Goitzane Marcaida; González, Juan R.; Rodríguez‐López, Raquel
Abstract: Background: SNRPN, which codes for the RNA‐binding SmN protein, is a candidate gene for Prader‐Willi syndrome. One characteristic of this neuroendocrine disorder is hyperphagia resulting in extreme obesity later in life. In the present study, we aimed to assess whether variability within this gene could be implicated in obesity susceptibility. Methods: A case–control study was performed including 265 unrelated patients with nonsyndromic and early‐onset severe obesity, belonging to high‐risk obesity families from Spanish ancestry; 184 healthy control individuals were included representative of the same genetic background and sex‐matched. Forty‐nine single nucleotide polymorphisms (SNPs) spanning the entire SNRPN gene were selected and genotyped using the Sequenom MassARRAY platform (Sequenom Inc., San Diego, CA, USA). Results: The four SNPs, rs12905653, rs752874, rs1391516 and rs2047433, were found to be nominally associated with obesity ( p < 0.03). The diversity haplotype distribution among cases and controls identified the combination rs12905653‐T/rs8028366‐A/rs4028395‐T as being strongly and inversely associated with obesity (odds ratio = 0.49; p = 0.0006). A genetic risk score was built based on rs12905653, rs1391516 and rs2047433 SNPs and each unit increase in genetic risk score increased the obesity risk by 49% (odds ratio = 1.49, 95% confidence interval = 1.24–1.80). Conclusions: To our knowledge, this is the first study reporting an association between variability in the SNRPN gene and the risk of being obese. Interestingly, it was the major allele of each SNP that was found to be associated with the risk of weight gain. Further studies analyzing this locus and the possible additive deleterious capability of SNP combinations could be useful for demonstrating the development of obesity.